Decision Support System for Determining Employee Salary Levels on CV. Rezeky Baru Service Lubuk Pakam using the Simple Additive Weighting (SAW) Method - Astry Rahayu (Institute of Computer Science, 2021)
Employees are viewed as one of the company's important assets and need to be managed and developed to support survival and achieve company goals. One form of employee organization that can be carried out by the company is to provide remuneration or salary payments that are appropriate for employees. Salary increases greatly affect employee motivation and productivity in carrying out and completing their work. To determine the amount of salary increase, a system is needed that can support decision making by managers. The use of decision support systems using simple additive weighting (SAW) method is very helpful for managers in making faster and more accurate decisions. The basic concept of the SAW method is to find the weighted sum of performance ratings in each alternative and on all attributes that require the decision matrix normalization process (X) to a scale that can be compared with all available alternative ratings. This method was chosen because it was able to select the best alternative from a number of alternatives based on the criteria determined by the research conducted by looking for weight values ​​for each configuration and then ranking that will determine the optimal alternative.